Prevalence of permanent first molar caries at Dental Hospital of Hasanuddin University: Prevalensi karies molar satu permanen di Rumah Sakit Gigi Mulut Pendidikan Universitas Hasanuddin - Sitoresmi, Merrysa; Dwiandhany, Wahyuni Suci; Jubhari, Eri Hendra (Makassar Dental Journal PDGI Makassar, 2024)
The permanent first molar is a very important tooth in the oral cavity because it plays a major role in chewing food, the key to occlu-sion, maintaining vertical facial dimensions, and anchors in orthodontic treatment. The purpose of this study was to determine the prevalence of caries in permanent first molar teeth. Qualitative research with descriptive observation method in cross sectional data obtained from medical records at RSGMP Hasanuddin University from January to October 2023. Data of 906 permanent mo-lar caries were obtained from 1,397 data with a prevalence of 64.85% in the Dental Conservation Polyclinic as much as 39.74%, female gender as much as 63.35%, in the age range of 15-34 years as much as 45.03% with a diagnosis of irreversible pulpitis as much as 47.02% and root canal treatment therapy as much as 72.19%. It is concluded that the prevalence of permanent first molar caries is most prevalent in the female gender with an age range of 15-34 years at the Dental Conservation Polyclinic with a diagnosis of irreversible pulpitis and root canal treatment therapy.